The social context of tobacco products use among adolescents in Lebanon (MedSPAD-Lebanon) - Naim Bejjani; Charbel El Bcheraoui; Salim M. Adib (Springer, 2019)
Background: Current data from the Middle East suggest a rapid increase in the incidence of smoking water-pipes (narguileh in Lebanon) in parallel with cigarettes. The social context in which these two behaviors are initiated and associated has not been studied. Methods: Data from a standardized questionnaire to measure the prevalence and practices related to cigarettes and narguileh consumption in a representative sample of 1097 children in grade 9 were extracted and analyzed for elements of the social context in which consumption occurs. Results and discussion: Among surveyed children (mean age 14.6), 3.9% were "frequent" cigarette smokers (more than nine times ever). Presence of parents and/or siblings who smoke is a key factor for initiation. Narguileh use is a social phenomenon, rarely smoked alone (<4%) with 19% of the surveyed children being "frequent" narguileh smokers (more than nine times ever). Almost half of these students (42%) have all their friends smoking narguileh. Conclusions: Further analysis confirmed that narguileh use is now an accepted familial and social phenomenon, with restrictions apparently decreasing. These results necessitate drawing strategies to address this public health concern that is becoming more prevalent in Lebanon and elsewhere in the Middle East.